2019
DOI: 10.1590/s0004-2803.201900000-72
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Surveillance of Helicobacter Pylori at the Biobío Region (Chile) in a Decade

Abstract: BACKGROUND: Helicobacter pylori infection in Chile remains as a public and private health-care system’s challenge, with a prevalence of the infection over 70%. Nowadays, antibiotic treatment of the infection is mandatory to prevent the arising of severe associated diseases but failures in the eradication therapy mainly due to clarithromycin resistance has been observed worldwide and first line eradication therapy seems to be not effective anymore in several geographical areas. Thus, health-care systems are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In the present review, no evolution of H. pylori resistance to amoxicillin was detected in most countries, such as Belgium, France, Russia, Australia, USA, Colombia, Chile and Taiwan [20][21][22][23][24][25][26][27][28][29][30][31][32]. It is noteworthy that no increase in amoxicillin resistance was observed in studies of treated patients in France (0.0% in 2014 and 2018, and 0.8% in 2016) and Taiwan (after one and two failed eradication attempts) [22,32].…”
Section: Resultscontrasting
confidence: 38%
“…In the present review, no evolution of H. pylori resistance to amoxicillin was detected in most countries, such as Belgium, France, Russia, Australia, USA, Colombia, Chile and Taiwan [20][21][22][23][24][25][26][27][28][29][30][31][32]. It is noteworthy that no increase in amoxicillin resistance was observed in studies of treated patients in France (0.0% in 2014 and 2018, and 0.8% in 2016) and Taiwan (after one and two failed eradication attempts) [22,32].…”
Section: Resultscontrasting
confidence: 38%
“…The high eradication success rate of HDDT in our study could be attributed to the following factors 1 : in Chile, the rate of resistance to amoxicillin is 4.2%, lower than clarithromycin resistance 21 . In the Eastern Mediterranean and Americas Region, the prevalence of primary amoxicillin resistance was relatively high, accounting for approximately 14% and 10% respectively, 22 this could reduce the efficacy of this therapy in the eradication of H. pylori 2 ; higher dosing frequency of the PPI dose (three times daily) has been associated with longer lasting anti‐acidic effects 23 . H. pylori has been shown to be more sensitive to antibiotics, when the gastric pH value is higher than six 3,24 ; the effect of PPI on inhibiting gastric acid secretion is affected by CYP2C19 gene polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the antibiotic treatment of infection by H. pylori is mandatory to prevent severe diseases; nevertheless, failures of the eradication therapy, particularly in the case of clarithromycin, have been observed worldwide [ 34 , 35 ]. In this respect, a study by our group indicated that clinical H. pylori isolates obtained in the Bio Bio region (Chile) from 2015 to 2017 were still highly sensitive to amoxicillin and tetracycline, but the resistance frequencies to clarithromycin (29.2%) and levofloxacin (20.8%) [ 36 ] suggested that the conventional triple therapy and therapeutic alternatives may not be effective in the Bio Bio region. A number of therapeutical alternatives have been investigated to prevent or to treat H. pylori infection [ 37 ].…”
Section: Discussionmentioning
confidence: 99%